Implementasi Sensor PH-4502C dan Sensor Suhu DS18B20 Untuk Pemantauan Air Kolam Nila - Pratama, Wayan Rio Adi; Dalimunthe, Ernando Rizki; Putri, Novia Utami (Department of Electrical Engineering, Faculty of Engineering, Universitas Lampung, 2025)
In cultivating freshwater fish, especially tilapia, water quality is a very important factor and influences the survival of the fish being farmed. Several parameters that must be considered in improving the development of tilapia fish are temperature and pH of the water. So, a water quality monitoring system is needed to be able to assess these parameters simultaneously in one time (real time) to maintain the quality of fish cultivation. The system designed for monitoring water quality uses a pH sensor with a 4502C module and a Ds18b20 temperature sensor which is then processed using an Arduino Uno so that it can be seen on the LCD. The results of designing a temperature and pH monitoring system carried out for three days in tilapia ponds obtained an error rate in measuring the pH of pond water of 0.87% on the first day, 0.94% on the second day, and 0.79% on the third day. Apart from pH measurements, the pool temperature was measured using a comparison of two Ds18b20 temperature sensors with research results showing the highest temperature measurement at 12.00 WIB was 30.25?C for three days.